Asparagine residue 368 is involved in Alzheimer's disease tau strain–specific aggregation - Shimonaka, Shotaro (J Biol Chem, 2020)
In tauopathies, tau forms pathogenic fibrils with distinct conformations (termed “tau strains”) and acts as an aggregation “seed” templating the conversion of normal tau into isomorphic fibrils. Previous research showed that the aggregation core of tau fibril covers the C-terminal region (243–406 amino acids (aa)) and differs among the diseases. However, the mechanisms by which distinct fibrous structures are formed and inherited via templated aggregation are still unknown. Here, we sought to identify the key sequences of seed-dependent aggregation. To identify sequences for which deletion reduces tau aggregation, SH-SY5Y cells expressing a series of 10 partial deletion (Del 1–10, covering 244–400 aa) mutants of tau-CTF24 (243–441 aa) were treated with tau seeds prepared from a different tauopathy patient's brain (Alzheimer's disease, progressive supranuclear palsy, and corticobasal degeneration) or recombinant tau, and then seed-dependent tau aggregation was assessed biochemically. We found that the Del 8 mutant lacking 353–368 aa showed significantly decreased aggregation in both cellular and in vitro models. Furthermore, to identify the minimum sequence responsible for tau aggregation, we systematically repeated cellular tau aggregation assays for the delineation of shorter deletion sites and revealed that Asn-368 mutation suppressed tau aggregation triggered by an AD tau seed, but not using other tauopathy seeds. Our study suggested that 353–368 aa is a novel aggregation-responsible sequence other than PHF6 and PHF6*, and within this sequence, the Asn-368 residue plays a role in strain-specific tau aggregation in different tauopathies.